Genome-wide identification and functional characterization of NPR1-like genes in Actinidia deliciosa - Weimin Zhong; Yuexia Wang; Shiming Han; Jihong Dong; Yumei Fang; Xiaoling Xu; Muhammad Umar Rasheed; Aiman Malik; Qurban Ali; Muhammad Ashfaq; Jia Zhou (PLoS ONE, 2025)
NPR1 (Nonexpresser of Pathogenesis-Related Genes 1) is a central regulator of salicylic acid (SA)-mediated defense signaling in plants and plays a pivotal role in modulating systemic acquired resistance (SAR). Despite its functional importance in biotic stress responses, a comprehensive understanding of the NPR1 gene family in Actinidia deliciosa (kiwifruit) has been lacking. In this study, we performed a genome-wide identification and characterization of NPR1 -like genes in A. deliciosa , identifying five candidate genes ( AdNPR1 – AdNPR5 ) containing conserved BTB/POZ and ankyrin repeat domains of NPR1 Protein. Phylogenetic analysis revealed that AdNPR3 and AdNPR4 grouped closely with AtNPR3 / AtNPR4 , indicating possible sub-functionalization related to pathogen-specific defense signaling. Conserved motif and gene structure analyses indicated strong structural conservation, while promoter analysis revealed diverse cis-regulatory elements associated with hormonal and stress responsiveness. Ka/Ks analysis suggested that the gene family evolved under strong purifying selection, with divergence events dating back to ~625 million years ago. Synteny and dual synteny mapping with Arabidopsis thaliana, Theobroma cacao, and Oryza sativa indicated segmental duplication as the primary driver of gene family expansion. Transcriptome profiling under B. cinerea (fungal) and Pseudomonas syringae pv. actinidiae (bacterial) infection demonstrated differential expression, particularly the upregulation of AdNPR3 and AdNPR4 , indicating their role in pathogen-induced defense responses. Gene Ontology enrichment and protein–protein interaction network analyses further confirmed the involvement of these genes in SA signaling, immune regulation, and floral development. This study provides foundational insights into the structural, evolutionary, and functional characteristics of NPR1 -like genes in A. deliciosa and highlights their potential as molecular targets for improving disease resistance in kiwifruit.